Multidisciplinary Approaches to Infection Control in Healthcare Management, Dentistry, Laboratory Services, Nursing, and Pharmacy - Awad Fawaz Awad Alharbi; Alaa Hassan Alkhamees; Fatima Abdel Wahed Al Faraj; Jabril Abdilaziz S Almutairi; Abdullah Mohammed Alassaf; Maryam Abdallah Ali Alsahw; Moeed Abdullah Al Amer; Haitham Faeasiri; Nasser Saad Alamri; Bashair Mohammed Aljubairy; Nada Shamrock Alotibi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Currently, infection control in the management of healthcare institutions is a combined effort of different disciplines that include healthcare management, dentistry, and pharmacy. This approach seeks to reduce its risks and promote HAI patients recovery and care quality in addressing the identified issues. Aim of work: To explore how healthcare management, dentistry, and pharmacycollaborate to prevent and manage infections, examining the unique contributions and synergistic efforts of each. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Multidisciplinary, Approaches, Infection Control, Healthcare Management, Dentistry, Laboratory Services, Nursing, and Pharmacy. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:Infection prevention and control is a team concept and this would involve collaboration between the Health care management, dentists, laboratory services, nurses, pharmacists and the technicians. All specializations have their pros and cons and make sure that the invention is adequately protected against infections. Thus, creating collaboration between different fields of healthcare allows for the establishment of protection of public safety and enhanced quality of the treatment received.